Land Degradation Enriches Soil δ13C in Alpine Steppe and Soil δ15N in Alpine Desert by Changing Plant and Soil Features on Qinghai‐Tibetan Plateau. Issue 4 (2nd July 2018) - Dong, Shikui; Li, Yu; Zhao, Zhenzhen; Li, Yuanyuan; Liu, Shiliang; Zhou, Huakun; Dong, Quanming; Li, Shuai; Gao, Xiaoxia; Shen, Hao; Xu, Yudan; Han, Yuhui; et al.
Abstract : Core Ideas: Alpine desert had higher soil δ 13 C and δ 15 N than alpine meadow and steppe. Soil δ13C and δ15N increased with depth in the alpine grasslands. Land degradation enriched the soil δ 13 C in the alpine steppe. Land degradation enhanced the soil δ 15 N in alpine desert. Plant and soil features were key for the dynamics of the soil δ 13 C and δ 15 N. Estimation of natural isotopic abundances can integrate across biogeochemical processes affecting the carbon and nitrogen dynamics in an ecosystem. Here, we investigated the natural isotopic abundances (δ 13 C and δ 15 N) of the soil in healthy and degraded alpine ecosystems, including alpine meadow, alpine steppe, and alpine desert on the Qinghai‐Tibetan Plateau (QTP). We also examined the effects of plant factors and soil chemical and physical factors on the soil δ 13 C and δ 15 N in these alpine ecosystems of the QTP. The results indicated that the soil δ 13 C and δ 15 N varied significantly with the grassland type, the land degradation, and soil depth. The C4‐plant dominated alpine desert was much higher in the soil δ 13 C and δ 15 N than the C3‐plant dominated alpine meadow and alpine steppe. Along the soil depth of 0 to 30 cm, the δ 13 C and δ 15 N were enriched in all types of the alpine ecosystems. The land degradation lowered the plant cover, aboveground plant biomass, soil organic carbon (SOC) and soil total nitrogen (TN) in all alpine ecosystems. Land degradation enriched the soil δ 13 C in the alpine steppe and the soil δ 15 N in alpine desert by changing their interactions with the plant and soil features.